UPAYA PENINGKATAN KREATIVITAS SISWA MELALUI IMPLEMENTASI BLENDED LEARNING PADA PEMBELAJARAN FISIKA KELAS VIIIA SMP NEGERI 1 MANTINGAN 2012/2013 - Listyowati Luntungan, Novi; Toro, Surantoro; Wahyuningsih, Daru (Jurnal Pendidikan Fisika, 2013)
Blended Learning models have been applied in form of. This Class Action Research is in two cycles. Itâs aims to improve : Student creativityÂ a class VIII A SMP Negeri 1 Mantingan school year 2012/2013 on Style of Materials. Data obtained through observation, interviews, creativity tests, making outline (summary), presentation, questionnaires, and review of documents. Itâs used quantitative and qualitative data analysis techniques. The conclution are : (1) Blended Learning can increase students creativity. It can be seen from average scores on the questionnaire students creativity in learning physics increased from 67.35 in pre-cycle, 81.30 first-cycle, and 89.22 in second-cycle. (2) Blended Learning models can improve the student creativity. It can be seen from the increased value of average student creativity tests of is 57.52 in pre-cycle, 60.35 first-cycle, and 77.74 in the second-cycle. It is also shown from the increasing of the average scores in making outline (summary) by the students that is 67.83 first-cycle and 77.61 second-cycle, while the average percentage of scores is 68.70 first-cycle and 75.43 second-cycle.These results have met the demand of Minimum Completeness Criteria (KMK) of SMP Negeri I Mantingan that is 70. Keywords : Blended Learning, Classroom Action Research (PTK), Studentsâ Creativity